ANALISIS PEMERIKSAAN LABORATORIUM PADA PENDERITA MALARIA - I Gede Wempi (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2012)
Malaria is the disease initially in the area of the Marsh called the disease of freshwater marshes. Scientific research on malaria make progress in their important first in 1880, when a French army doctor working in the military hospital of Constantine in Algeria named Charles Louis Alphonse Laveran observed parasites for the first time, inside the red blood cells of people suffering from malaria. This paper outlines some of the diagnostic screening for malaria. Examination of the diagnosis of malaria as gold standard still not satisfactory as found parasitic blood through thin blood test. Examination of malaria in outline there are three, namely for microscopic examination examination serologis and examination of dna. 1. Microscopic examination is still a standard gold for enforcement the diagnosis of diseases malaria. 2. Examination serologis detection using an antibody; detection techniques antibody can not tell that infection ' s going on but could have an antibody that detected is notching reaction immunologi of infection in the past. Meanwhile, with the technique of a spesific antigen can't portray degrees parasitemia patients. 3. DNA (PCR) , more sensitive to a plasmodium but the weakness this technique is clear to financing costs and not all laboratory can do checking this.